Investment Analysis And Economic Benefits Of Depressurisation Strategies For Enhanced Slope Stability And Optimization Of Coal Mine Slopes - Reynara Davin Chen; Oktofa Yudha Sudrajad (UNIVED Press, 2026)
PT OPQ aims to increase its coal production target from 50 million tons in 2025 to 100 million tons in 2030 to meet both domestic and export market demand which aligns to the strategic direction from management. However, because of the geological and hydrogeological constraints and land limitations in Pit BU, there are only so many optimizations that can be done with just technical evaluations. It is necessary to conduct a thorough economic feasibility assessment to identify if the chosen operational approach can be executed profitably within the framework of the company’s long term business goals. Given the constraints that PT OPQ faces in PIT BU, the consideration of investment feasibility, driven through technical data in assessment of slope depressurization hipothetical scenarios, from a geological, hydrogeological and mine planning perspective, is paramount. Equally, having such a complex technical assessment requires a financial counterpart. This is the purpose of the study, to construct a financial model based on Discounted Cash Flow, with the Payback Period, Discounted Payback Period, Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI) as the key decision parameters. To understand the effect of market fluctuations and operational risk with respect to the investment’s feasibility, sensitivity analysis and Monte Carlo simulation were conducted. Analyzing the financial risk from the NPV also indicates the least risk to the finances of the business from the base case scenario. Therefore, the choice of depressurization (Option 2) compared to continued operation without depressurization (Option 1) illustrates that there is greater financial potential. In the worst case, there is still a minor loss of financial potential for a scenario exhibiting the dependence on the price of coal. Thus, the approach for depressurization is the best for the medium term, though there needs to be a reconsideration of the cost of the coal, the coal from the closed mine, the loss of volatility of the coal, and the mining of coal.